1970
DOI: 10.1037/h0029326
|View full text |Cite
|
Sign up to set email alerts
|

Responses of adult and immature rats to sex odors.

Abstract: Among normal or castrated male rats, 56 sex-experienced and 60 naive rats showed no preference for normal vs. castrated male odors. In a second study, 24 naive receptive females preferred nonreceptive over receptive female odors (p < .05), but 25 naive nonreceptive and 42 experienced females showed no preference. In a third study, 50 immature males injected with testosterone preferred receptive over nonreceptive female odors (p < .01), but 40 placebo-injected rats showed no preference. Thirty immature males pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
1

Year Published

1972
1972
2004
2004

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 11 publications
1
20
1
Order By: Relevance
“…Studies that fail to include individuals across all age categories are likely to lose valuable information about the changing role of social odours during different developmental stages. Although few studies examine developmental effects on odour discrimination, results generally show that as reproductive maturity is reached, preference for heterosexual odours increases (Carr, Wylie & Loeb, 1970;Drickamer & Brown, 1998). These odour preferences often develop in parallel with more general preferences for the opposite sex (Matuszczyk, Appa & Larsson, 1994), presumably because before reproductive maturity is reached, the individual does not perceive the opposite sex as a potential mate.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that fail to include individuals across all age categories are likely to lose valuable information about the changing role of social odours during different developmental stages. Although few studies examine developmental effects on odour discrimination, results generally show that as reproductive maturity is reached, preference for heterosexual odours increases (Carr, Wylie & Loeb, 1970;Drickamer & Brown, 1998). These odour preferences often develop in parallel with more general preferences for the opposite sex (Matuszczyk, Appa & Larsson, 1994), presumably because before reproductive maturity is reached, the individual does not perceive the opposite sex as a potential mate.…”
Section: Introductionmentioning
confidence: 99%
“…One might also expect chemosensory discrimination patterns to change with age, as the functional significance of odours varies between adult and subadult animals (Carr, Wylie & Loeb, 1970;Fillon & Bass, 1985;Drickamer, 1989Drickamer, , 1997Hurst, 1990b;Drickamer & Brown, 1998). For example, Solomon & Rumbaugh (1997) found that as pine voles reach maturity they shift from a preference for familiar family odours to a preference for odours from unfamiliar opposite-sexed individuals, and suggest that this shift is related to changing motivational and functional priorities.…”
Section: Introductionmentioning
confidence: 99%
“…The reinforcement and withholding of reinforcement from a predecessor have also been shown to be conditions producing odors which can serve as conditioned stimuli for discrimination using runways (Ludvigson and Sytsma, 1967), and T-mazes (Morrison and Ludvigson, 1970). Male rats prefer odors from sexually receptive females to those from unreceptive females and males (LeMagnen, 1952;Carr, Loeb, and Dissinger, 1965;Carr, Wylie, and Loeb, 1970), and surfaces on which socially submissive animals have had contact are preferred over those from dominant rats (Krames, Carr, and Bergman;.…”
mentioning
confidence: 99%